2020
DOI: 10.1080/09593985.2019.1710883
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the factors influencing physiotherapists’ attitudes towards working with people living with dementia

Abstract: This is a repository copy of Understanding the factors influencing physiotherapists' attitudes towards working with people living with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 26 publications
(23 reference statements)
1
25
0
Order By: Relevance
“…This study's findings show limited level of knowledge of dementia (an average of 64.4% correct answers across the entire sample) among the sample population. This is notably much lower than other studies assessing dementia knowledge among physiotherapists in Canada, and Australia as well as other healthcare professionals in China and in India (Biswas et al, 2017;Hunter & Divine, 2020;Maggs, Kay & Ovaskainen, 2019;Wang et al, 2018). Descriptive analysis of the DKAT2 items showed the areas in dementia that are generally wellknown, and areas hardly known and easily confused about.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…This study's findings show limited level of knowledge of dementia (an average of 64.4% correct answers across the entire sample) among the sample population. This is notably much lower than other studies assessing dementia knowledge among physiotherapists in Canada, and Australia as well as other healthcare professionals in China and in India (Biswas et al, 2017;Hunter & Divine, 2020;Maggs, Kay & Ovaskainen, 2019;Wang et al, 2018). Descriptive analysis of the DKAT2 items showed the areas in dementia that are generally wellknown, and areas hardly known and easily confused about.…”
Section: Discussionmentioning
confidence: 64%
“…Studies on the knowledge of dementia among physiotherapists have been carried out in countries like Australia, The United Kingdom, Ireland, The United States of America and Canada. Hunter and Divine (2020) in a Canadian survey highlighted that out of 36% of physiotherapists who had received a prior training on dementia either as part of their physiotherapy degree program or other outside courses, 40% of them felt they needed additional training in order to effectively treat people with dementia ( Hunter & Divine, 2020 ). Similar findings were reported in studies ( Lorio, Gore, Warthen, Housley, & Burgess, 2017 ; Miles, Staples & Lee, 2019 ) carried out in the United States which assessed the knowledge and attitude of physiotherapists towards dementia care.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, knowledge of dementia was positively associated with attitude toward dementia and psychological wellbeing, and it was identified to be a direct predictor of attitude toward dementia. Even though no caregiver evidence has been identified from previous research, this finding can be partially explained by a study conducted among physiotherapists, which indicates that the more they were educated about dementia knowledge, the more positive attitudes they would have ( 31 ). However, a different opinion was identified by a study in Ireland, which found that greater knowledge of dementia does not ensure a positive attitude toward dementia among the general public ( 32 ).…”
Section: Discussionmentioning
confidence: 88%